NCOG-12. IMPACT OF TUMOR-RELATED SEIZURES ON MENTAL HEALTH DISORDER ORDER IN LOW-GRADE GLIOMA. (14th November 2022) - Bhanja, Debarati; Ba, Djibril; Tuohy, Kyle; Wilding, Hannah; Trifoi, Mara; Padmanaban, Varun; Liu, Guodong; Sughrue, Michael; Zacharia, Brad; Leslie, Douglas; Mansouri, Alireza
Abstract: INTRODUCTION: Majority of LGG patients experience seizures during their disease course, requiring anti-epileptic drugs (AEDs). Frequent seizures negatively impact health-related quality of life (HRQoL). AEDs, moreover, are hypothesized to have mood-modulating effects. As survival for LGG patients has been improving, it is essential that the impact of seizure burden and AEDs on mental health disorders (MHD) be considered. The objective was to measure an association of tumor-related seizures with MHD onset among LGG patients. METHODS: This retrospective cohort study queried data from the IBM Watson Health MarketScan® Claims and Encounters Database (2005-2014) to identify LGG patients without prior MHD history who experienced glioma-related seizures. Presence of seizures was determined by anti-epileptic drug fills within one year following LGG diagnosis. Patients with new onset of MHDs were identified using ICD-9 codes for MHDs and psychotropic drug fills in the 12 months post-LGG diagnosis period. Unadjusted odds ratios measured associations between seizures and MHD prevalence. RESULTS: 11, 458 LGG patients with no history of MHD were included; 1, 799 (15.7%) experienced seizures within 12 months of LGG diagnosis. Among them, 494 (27.5%) developed MHD in the post-LGG diagnosis period. Patients who experienced seizures were more likely to develop an MHD compared to patients who did not (OR, 2.19, 95% CI, 1.95–2.47). MHD incidence was significantly associated with female gender (OR, 1.14, 95%, 1.03–1.26) and age range of 35–44 (OR, 1.20, 95%, 1.03–1.39) compared to 18–34. CONCLUSION: These findings demonstrated that tumor-related seizures were associated with MHD onset. This highlights the burden of seizures and regular AED use on mental health. The psychosocial and neurological aspects related to seizures and AEDs likely contribute to the multifaceted mental health disorder onset seen among these LGG patients. Proactive counseling, diagnosis, and management of MHDs in LGGs, particularly those with seizures, is warranted.